A comparative study of thermal performances of three mud dwelling units with courtyards in composite climate. Issue 3 (3rd July 2017) - Gupta, Janmejoy; Chakraborty, Manjari; Paul, Arnab; Korrapatti, Vamsi
Abstract: Jharkhand is a state in the eastern part of India. The tropic of Cancer (23 and a half degree north line) passes through Ranchi district in Jharkhand. Mud huts with burnt clay tiled roofs in Ranchi district in Jharkhand are an integral component of the state's vernacular architecture. They come in various shapes, with a number of them having a courtyard type of plan. In general, it has been stated that courtyard type dwelling units show better thermal performance during summer and winter. In this paper, three types of mud huts with courtyards are taken as a study and through temperature measurements in the south side rooms and "Ecotect-Autodesk" (Version 2011) software simulations, their thermal performance during the hotter and colder parts of the year are observed. Thereafter, based on the study, the thermally better performing dwelling types in summer and winter are identified among the three sub-types studied. It is found that all courtyard type dwellings do not necessarily show better thermal performance in summer and winter in composite climate. Certain recommendations with respect to increasing thermal comfort in general in courtyard type huts are made.